Effect of heart rate on shooting performance in elite archers - Açikada, C.; Hazir, T.; Asçi, A.; Aytar, S. H.; Tinazci, C. (Heliyon, 2019)
Aim: The aim of the present study was to examine the effect of heart rate on shooting performance in elite archers. Methods: Regularly trained 13 (7 female, 6 male) international level elite archers performed a (specific) protocol twice with 3 days interval in an indoor area. In order to raise the heart rate (HR) and related physiological stress the archers performed 4 sets of steady pace shuttle runs (males 10 km h-1; females 8 km h-1) for 3 minutes in a 20 m course following with 1 minute stop during which they performed 3 shots to 18 meter distance indoor target, and followed by 1 minute rest, where blood sample was collected from ear lobe for blood lactate (BL) analysis. Heart rate monitors were used for heart rate (HR) recordings with 5 seconds intervals for resting, running, shooting, and recovery periods. The score of the shots were recorded as in the normal archery indoor competition. Average (overall) results were taken into account for statistical analysis. Results: Mean HR and BL during resting shoot in 1st and 2nd tests were 119.0 and 112.2 bpm (range 1st test: 101-142 bpm, 2nd test: 96-135 bpm) and 1.72 and 1.65 mmol.L-1 (range 1st test: 0.9-2.6 mmol.L-1, 2nd test: 0.8-2.3 mmol.L-1) respectively. Mean HR and BL during post exercise shooting in 1st and 2nd tests were 168 and 166 bpm (range 1st test: 152-191 bpm, 2nd test: 147-188 bpm) and 4.21 and 3.44 mmol.L-1 (range 1st test: 1.3-7.0 mmol.L-1, 2nd test: 1.3-5.7 mmol.L-1) respectively. There was not any statistically difference between shooting scores (27.50-27.23 points) after running exercise and resting (p > 0.05). Conclusion: It was concluded that, under simulated indoor competition environment, high HR values do not influence short distance shooting scores.